COMPARATIVE ANALYSIS OF CONVENTIONAL AND LIQUID-BASED CYTOLOGICAL METHODS FOR CERVICAL SMEARS - N. N. Volchenko; T. V. Sushinskaya; O. V. Borisova; V. Yu. Melnikova; A. N. Petrov (Исследования и практика в медицине, 2019)
Purpose. Comparative analysis of the diagnostic value of traditional cytology (TC) and liquid cytology (LC) in the identification of cervical intraepithelial neoplasia (CIN) and cervical cancer (CC).Patients and methots. The study included 87 women aged 18 to 80 years. All women were referred with suspicion of CIN, or underwent a control cytological examination after treatment for CIN and cervical cancer. Smears were taken separately from ecto-, endocervix and mixed. Various tools were used (trowel, brushes type D, F and Cervex-Brush Combi). Each patient was sampled at the same time by different types of instruments. All surveyed women were performed at the same time traditional and fluid cytology. Liquid preparations were prepared using SurePath™ technology (BD and Company, Netherlands, USA) and E‑Prep (Biodyne, South Korea). Traditional cytological preparations were stained according to the Pappenheim method, liquid preparations — by Papanicolaou. A comparative analysis of cytological and histological findings was carried out.Results. According to our data, the number of non-informative material practically coincides in the shopping center and in the LC, from the instruments used the best results were obtained when using a cytobrush of type D and a wooden spatula. The frequency of detection of CIN squamous epithelium in the LC is somewhat less than in the shopping center (60% vs. 62%). This is due to the lack of experience in evaluating the life cycle drugs. Despite the fact that the overall frequency of CIN detection is somewhat lower in the LC than in the TC, the frequency of detection of high grade squamous intraepithelial lesion (HSIL) is higher in the LC (51% versus 46%). This is due to the fact that cellular elements are concentrated in a limited area and single small HSIL complexes that are missed in the shopping center are better detected in the LC. The sensitivity of the TC smear from the cervix was 96.2%, life cycle — 92.4%. The accuracy of the shopping center is 92%, the life cycle is 89.6%.Conclusion. LC is an alternative to traditional cytological examination in order to detect pretumor diseases and cervical cancer. For an objective assessment of liquid preparations, additional training of cytologists is necessary.